Formal principles in the music of Brahms - Pascall, R; Pascall, Robert (1973)
﻿ Part 1 of the succeeding work deals with aspects of form which are neither binary nor ternary In basis, and concerns Itself with the addition of sections of music which are either disparate or basically alike. Multi-movement works in instrumental music have certain conventions with regard to the number of movements and with regard to the sequences in these movements of speeds, tonalities and forms. Pressures for unity within such basically discrete works may manifest themselves by thematic quotation, thematic metamorphosis or motific similarities between movements. Slow introductions are necessarily harmonically wayward and are mostly thematically connected with the subsequent part of the movement... (see thesis for the rest of the abstract)